Determinants of poverty during transition: household survey evidence from Ukraine - Tilman Brück; Alexander M. Danzer; Alexander Muravyev; Natalia Weißhaar (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The paper analyzes the incidence, the severity and the determinants of household poverty in Ukraine during transition using two comparable surveys from 1996 and 2004. We measure poverty using income and consumption and contrast the effects of various poverty lines. Poverty in both periods follows some of the determinants commonly identified in the literature, including greater poverty among households with children and with less education. We also identify specific features of poverty in transition, including the relatively low importance of unemployment and the existence of poverty even among households with employment. Poverty determinants change over time in line with the experience of transition and restructuring.
Keywords: P20; I32; J20; O15; 330; poverty; transition; survey; Ukraine; Armut; Übergangswirtschaft; Ukraine